The decoration of the dining room - Randle, Elizabeth (My University, 1907)
Introduction: The Dining Room in many homes is the most important room in the house. Here the entire family gather, perhaps three times a day and for that reason the room should be as pleasant as possible and represent something of comfort and happiness. There should be no airy triflings either in color or fabrics and no fussy fancywork. Two of the most important things in a Dining Room are, an abundance of light and proper ventilation. A western exposure is not preferable for a dining room. It makes the room a rather cheerless one on a winter's morning, and in the summer, by the time the family gather for the evening meal, the rays of the setting sun are likely to interfere with their comfort. A natural lighting consisting of a southerly or easterly aspect is much to be preferred. In artificial lighting use and appropriateness must be the first consideration. The primary object is to light the room in the right place without allowing the glare of light to strike the eye unpleasantly. Electric lights can be dropped from the ceiling, or if the light is on the table one should have the shade so it can be adjusted. Light should always be softened before it comes into the eyes. In the Dining Room the purpose is to light the table. This may be done in two ways; by hanging the light from the ceiling, or by having a lamp or candles on the table. A candle stick must have: first,- something to hold the candle; second,- something to catch the drip; third,- something to hold candle by. The lamp in this room should not be elaborate. A round lamp and a round globe give monotony. It is better to have different shapes that give variety. Highly decorated lamps should be avoided and in their place the dull hues might be used. The bowl of lamp must not be so large as to shade the table around it. In lighting by electricity the chandelier should hang directly over the table and the light be softened by ground glass shades.
Citation: Randle, Elizabeth. The decoration of the dining room. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Dining Room; Dining Room Decorations; Home Decorations; Theses